A CBCT Assessment of Apical Transportation in Root Canals Prepared with Hand K-Flexofile and K3 Rotary Instruments - Madani, Zahra Sadat (Iran Endod J, 2015)
Introduction: Apical transportation changes the physical shape and physiologic environment of the root canal terminus. The aim of the present experimental study was to determine the extent of apical transportation after instrumentation with hand K-Flexofile and K3 rotary instruments by means of cone-beam computed tomography (CBCT). Methods and Materials: Forty mesiobuccal root canals of maxillary first molars, with 19-22 mm length and 20-40(°) canal curvature, were selected and assigned into two preparation groups. The first group was prepared with K-Flexofile with passive step-back technique and the second group was prepared with K3 rotary instruments. Pre and post instrumentation CBCT images were taken under similar conditions. The amount of root canal transportation was evaluated by Mann-Whitney U test and the chi-square test was used for the qualitative evaluation. Results: The amounts of apical canal transportation with the K3 and K-Flexofile instruments were 0.105±0.088 and 0.150±0.127 mm, respectively with no statistically significant differences. In the manual technique, 25% of the canals had no apical transportation; while 30% of the canals in the K3 group were transportation free. Conclusion: Both systems were able to preserve the initial curvature of the canals and both had sufficient accuracy. Preparation with K3 rotary instruments resulted in apical transportation similar to that of K-Flexofile.